Two-dimensional particles, conductive film, conductive paste, and composite material

CN118382599BActive Publication Date: 2026-11-03MURATA MFG CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202280082647.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-12-16
Filing Date
2022-12-06
Publication Date
2026-11-03
Estimated Expiration
2042-12-06

AI Technical Summary

Technical Problem

现有MXene材料在除去Li+后,仍然存在吸湿问题,导致电导率降低,无法满足薄膜的电导率要求。

Method used

Two-dimensional particles containing a specific ratio of Li atoms and phosphorus atoms are used. The ratio of Li atoms is controlled by measuring the chemical shift using 7Li NMR. Layering is performed to form monolayer or few-layer MXene particles. Combined with the presence of phosphorus atoms, the moisture resistance and conductivity of the material are improved.

Benefits of technology

A conductive film that maintains high conductivity even after prolonged exposure to high humidity conditions has been developed, making it suitable for applications requiring high conductivity and high moisture resistance, such as electrodes for RFID antennas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118382599B_ABST
    Figure CN118382599B_ABST
Patent Text Reader

Abstract

The present invention aims to provide a two-dimensional particle capable of realizing a conductive film having high conductivity and moisture resistance. The two-dimensional particle of the present invention is a two-dimensional particle having one or more layers, the two-dimensional particle containing Li atoms, the layer containing a layer main body represented by the formula: M m X n a modification or a terminal T (T is at least one selected from a hydroxyl group, a fluorine atom, a chlorine atom, an oxygen atom, and a hydrogen atom) present on the surface of the layer main body, M is at least one metal of Groups 3, 4, 5, 6, and 7, X is a carbon atom, a nitrogen atom, or a combination thereof, n is 1 or more and 4 or less, m is greater than n and 5 or less, and the Li atoms contain a first component and a second component having a chemical shift larger than the first component as measured by Li NMR, the proportion of the first component in the total of the first component and the second component being 17 atomic % or more and 70 atomic % or less. 7 Li NMR measurement, the proportion of the first component in the total of the first component and the second component being 17 atomic % or more and 70 atomic % or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to two-dimensional particles, conductive films, conductive pastes, and composite materials. Background Technology

[0002] In recent years, MXene has attracted much attention as a novel conductive material. MXene is a so-called two-dimensional material, as described below, which is a layered material with one or more layers. Typically, MXene exists in the form of particles (which can include powders, flakes, nanosheets, etc.) of this layered material.

[0003] Currently, various studies are underway regarding the application of MXene in various electrical devices. For these applications, there is a need to further improve the conductivity and moisture resistance of MXene-containing materials. As part of this research, cleaning methods for MXene are being investigated.

[0004] Non-patent document 1 describes a method for removing Li by cleaning MXene in the presence of acid. + The content.

[0005] Existing technical documents

[0006] Non-patent literature

[0007] Non-patent document 1: Hongwu Chen, et al., "Pristine Titanium Carbide MXene Films with Environmentally Stable Conductivity and Superior Mechanical Strength" Adv.Mater.2020, 30, 1906996 Summary of the Invention

[0008] The problem that the invention aims to solve

[0009] In the MXene described in Non-Patent Document 1, although Li was removed + However, due to moisture absorption, the conductivity decreases by about 20%. In addition, the conductivity of the MXene described in Non-Patent Document 1 cannot be adequately satisfied.

[0010] The object of this invention is to provide a two-dimensional particle capable of producing a conductive film with high conductivity and moisture resistance. Furthermore, the object of this invention is to provide conductive films, conductive pastes, and conductive composite materials using this two-dimensional particle.

[0011] Methods for solving problems

[0012] This invention includes the following:

[0013] [1] A two-dimensional particle, which is a two-dimensional particle having one or more layers.

[0014] The two-dimensional particles contain Li atoms.

[0015] The above layer includes the following formula: M m X n The layer shown includes the main body of the layer and the modifications or terminals T (T being at least one selected from hydroxyl, fluorine, chlorine, oxygen, and hydrogen atoms) present on the surface of the main body of the layer.

[0016] (Formula M) m X n In this context, M is at least one metal from Groups 3, 4, 5, 6, or 7.

[0017] X is a carbon atom, a nitrogen atom, or a combination thereof.

[0018] n is 1 or more and 4 or less

[0019] (m is greater than n and less than 5),

[0020] Li atoms contain the first component and through 7 The second component, whose chemical shift is greater than that of the first component as determined by Li NMR,

[0021] The proportion of the first component in the total of the first component and the second component is 17 atomic% or more and 70 atomic% or less.

[0022] [2] According to the two-dimensional particle described in [1], wherein the above-mentioned through 7 The chemical shift of the first component, as determined by Li NMR, is less than 0.6 ppm. 7 The chemical shift of the second component, as determined by Li NMR, is greater than 0.6 ppm and less than 2.0 ppm.

[0023] [3] According to the two-dimensional particles described in [1] or [2], they contain phosphorus atoms.

[0024] [4] The two-dimensional particle described in any one of [1] to [3], wherein the content of the above-mentioned phosphorus atoms is 0.1% by mass or more and 14% by mass or less.

[0025] [5] According to any one of [1] to [4], the two-dimensional particle is PO4. 3- Its form.

[0026] [6] According to any one of [1] to [5], the average thickness of the two-dimensional particle is more than 1 nm and less than 10 nm.

[0027] [7] A conductive film comprising two-dimensional particles described in any one of [1] to [6].

[0028] [8] A conductive paste comprising two-dimensional particles described in any one of [1] to [6].

[0029] [9] A conductive composite material comprising two-dimensional particles described in any one of [1] to [6] and a resin.

[0030] Invention Effects

[0031] According to the present invention, two-dimensional particles capable of producing conductive films with high conductivity and moisture resistance can be provided. Furthermore, the present invention can provide conductive films, conductive pastes, and conductive composite materials using these two-dimensional particles. Attached Figure Description

[0032] Figure 1 This is a schematic cross-sectional view showing MXene particles of a layered material in one embodiment of the present invention. Figure 1 (a) represents a monolayer MXene particle. Figure 1 (b) represents multi-layer (e.g., two-layer) MXene particles.

[0033] Figure 2 This is a schematic cross-sectional view illustrating a conductive film in one embodiment of the present invention. Detailed Implementation

[0034] (Implementation Method 1: Two-Dimensional Particles)

[0035] The following describes in detail a two-dimensional particle in one embodiment of the present invention, but the present invention is not limited to this embodiment.

[0036] The two-dimensional particles in this embodiment are two-dimensional particles of layered material with one or more layers, containing Li atoms.

[0037] The above layer includes the following formula: M m X n The layer body shown (which may have a lattice in which each X is located within an octahedral array of M) and the modifications or terminations T (T being at least one selected from hydroxyl, fluorine, chlorine, oxygen and hydrogen atoms) present on the surface of the layer body (more specifically, at least one of the two opposing surfaces of the layer body)

[0038] (Formula M) m X n In this context, M is at least one metal from Groups 3, 4, 5, 6, or 7.

[0039] X is a carbon atom, a nitrogen atom, or a combination thereof.

[0040] n is 1 or more and 4 or less

[0041] (m is greater than n and less than 5),

[0042] Li atoms contain the first component and through... 7 The second component, whose chemical shift is greater than that of the first component as determined by Li NMR (nuclear magnetic resonance),

[0043] The proportion of the first component in the total of the first component and the second component is 17 atomic% or more and 70 atomic% or less.

[0044] Therefore, the conductive film obtained using the two-dimensional particles of the present invention exhibits high conductivity and good moisture resistance. In the present invention, moisture resistance refers to the ability to maintain conductivity even after prolonged exposure to high humidity conditions. Furthermore, electrodes comprising this conductive film can be used for applications requiring high conductivity and high moisture resistance, such as antenna electrodes, and particularly electrodes for RFID (radio frequency identifier).

[0045] In this invention, when an element is referred to as an "atom", the oxidation number of the element is not limited to 0, but can be any number within the range of possible oxidation numbers of the element.

[0046] The aforementioned layered material can be understood as a layered compound, also referred to as "M". m X n T s s is any number; in the past, x or z were sometimes used instead of s. Typically, n can be 1, 2, 3, or 4, but is not limited to these.

[0047] In the above formula of MXene, M is preferably selected from at least one of Ti, Zr, Hf, V, Nb, Ta, Cr, Mo and Mn, and more preferably from at least one of Ti, V, Cr and Mo.

[0048] Regarding MXene, the above formula is known: M m X n MXene can be represented as follows.

[0049] Sc2C, Ti2C, Ti2N, Zr2C, Zr2N, Hf2C, Hf2N, V2C, V2N, Nb2C, Ta2C, Cr2C, Cr2N, Mo2C, Mo 1.3 C, Cr 1.3 C, (Ti, V)2C, (Ti, Nb)2C, W2C, W 1.3 C, Mo2N, Nb 1.3C, Mo 1.3 Y 0.6 C (In the above formula, "1.3" and "0.6" refer to approximately 1.3 (=4 / 3) and approximately 0.6 (=2 / 3), respectively). , Ti3C2, Ti3N2, Ti3(CN), Zr3C2, (Ti, V)3C2, (Ti2Nb)C2, (Ti2Ta)C2, (Ti2Mn)C2, Hf3C2, (Hf2V)C2, (Hf2Mn)C2, (V2 Ti)C2, (Cr2Ti)C2, (Cr2V)C2, (Cr2Nb)C2, (Cr2Ta)C2, (Mo2Sc)C2, (Mo2Ti)C2, (Mo2Z r)C2, (Mo2Hf)C2, (Mo2V)C2, (Mo2Nb)C2, (Mo2Ta)C2, (W2Ti)C2, (W2Zr)C2, (W2Hf)C2,

[0050] Ti4N3, V4C3, Nb4C3, Ta4C3, (Ti, Nb)4C3, (Nb, Zr)4C3, (Ti2Nb2)C3, (Ti2Ta2)C3, (V2Ti2)C3, (V2Nb2)C3, (V2Ta2)C3, (Nb2Ta2)C3, (Cr2Ti2)C3, (Cr2V 2)C3, (Cr2Nb2)C3, (Cr2Ta2)C3, (Mo2Ti2)C3, (Mo2Zr2)C3, (Mo2Hf2)C3, (Mo2V2)C3, (Mo2Nb2)C3, (Mo2Ta2)C3, (W2Ti2)C3, (W2Zr2)C3, (W2Hf2)C3, (Mo 2.7 V 1.3 In the above formula, "2.7" and "1.3" refer to approximately 2.7 (=8 / 3) and approximately 1.3 (=4 / 3), respectively.

[0051] Representatively, in the above formulas, M can be titanium or vanadium, and X can be a carbon atom or a nitrogen atom. For example, the MAX phase is Ti3AlC2, and MXene is Ti3C2T. s (In other words, M is Ti, X is C, n is 2, and m is 3).

[0052] It should be noted that in this invention, MXene may contain a relatively small amount of A atoms from the MAX phase of the precursor, for example, less than 10% by mass relative to the original A atoms. The residual amount of A atoms is preferably less than 8% by mass, more preferably less than 6% by mass. However, even if the residual amount of A atoms exceeds 10% by mass, there may be situations where there are no problems depending on the application and conditions of use of the two-dimensional particles.

[0053] In this invention, the above-mentioned layer is sometimes referred to as the MXene layer, and the above-mentioned two-dimensional particles are sometimes referred to as MXene two-dimensional particles or MXene particles.

[0054] The two-dimensional particles in this embodiment include Figure 1 The diagram in (a) schematically illustrates an aggregate of MXene particles (hereinafter simply referred to as "MXene particles") 10a (monolayer MXene particles). More specifically, MXene particles 10a are MXene layer 7a, which has M m X n The layer body shown (M) m X n Layer 1a, and the modifications or ends T3a, 5a present on the surface of the layer body 1a (more specifically, at least one of the two opposing surfaces in each layer). Therefore, the MXene layer 7a is also referred to as "M". m X n T s , where s is any number.

[0055] The two-dimensional particle in this embodiment can comprise one or more layers. As a multi-layered MXene particle, such as... Figure 1 As illustrated in (b), two layers of MXene particles 10b can be cited, but are not limited to these examples. Figure 1 In (b), 1b, 3b, 5b, and 7b are the same as those mentioned above. Figure 1 (a) 1a, 3a, 5a, and 7a are the same. Two adjacent MXene layers (e.g., 7a and 7b) of multilayer MXene particles do not need to be completely separated, but can be in partial contact. The MXene particle 10a mentioned above is a particle that exists as a single layer when each of the multilayer MXene particles 10b is separated, with some unseparated multilayer MXene particles 10b remaining, forming a mixture of the single-layer MXene particles 10a and the multilayer MXene particles 10b.

[0056] Not limited to this embodiment, the thickness of each layer (corresponding to the MXene layers 7a and 7b described above) contained in the MXene particles is, for example, 0.8 nm or more and 5 nm or less, particularly 0.8 nm or more and 3 nm or less (mainly depending on the number of M-atom layers contained in each layer). For each stack of multilayer MXene particles that may be included, the interlayer distance (or void size, in Figure 1 (in (b) denoted by Δd) can be, for example, greater than 0.8 nm and less than 10 nm, especially greater than 0.8 nm and less than 5 nm, even more particularly about 1 nm, and the total number of layers can be greater than 2 and less than 20,000.

[0057] The two-dimensional particles in this embodiment are preferably MXene particles with fewer layers, obtained by layering the aforementioned multi-layer MXene particles. "Fewer layers" means, for example, that the number of MXene layers is 6 or less. Furthermore, the thickness of the multi-layer MXene particles with fewer layers in the stacking direction is preferably 15 nm or less, and more preferably 10 nm or less. Hereinafter, these "multi-layer MXene particles with fewer layers" are sometimes referred to as "few-layer MXene particles." Additionally, single-layer MXene particles and few-layer MXene particles are sometimes referred to together as "single-layer / few-layer MXene particles."

[0058] The two-dimensional particles in this embodiment preferably include monolayer MXene particles and few-layer MXene particles, i.e., monolayer and few-layer MXene particles. In the two-dimensional particles of this embodiment, the proportion of monolayer and few-layer MXene particles with a thickness of 15 nm or less is preferably 90% by volume or more, and more preferably 95% by volume or more.

[0059] The above-mentioned Li atoms include the first component and through 7 The second component, whose chemical shift is greater than that of the first component as determined by Li NMR, has a proportion of the first component in the total of the first and second components that is 17 atomic percent or more and 70 atomic percent or less. This enables the realization of a conductive film with high conductivity and moisture resistance.

[0060] The proportion of component 1 in the total of component 1 and component 2 can be determined by... 7 Li NMR was used for determination. For example, in 7 In a Li NMR spectrum, when the relative area of ​​the peaks belonging to the first component is set as S1 and the relative area of ​​the peaks belonging to the second component is set as S2, the proportion of the first component in the total of the first and second components can be calculated in the form of S1 / (S1+S2). In one method, 7 The cumulative delay time for Li NMR measurements was set to 4 seconds.

[0061] Although not bound by a specific theory, it is believed that the first component is bound by water and exists in a state with low degrees of freedom, while the second component is loosely adsorbed on the surface of the two-dimensional particles and exists in a state with relatively high degrees of freedom. Furthermore, it is believed that by having the first and second components coexist in a specific ratio, monolayer or few-layer structures can be achieved, and water adsorption can be prevented, thereby exhibiting high electrical conductivity and high moisture resistance.

[0062] The degrees of freedom of the first and second components can be confirmed, for example, by comparing their T2 relaxation times (spin-spin relaxation times). While not bound by a specific theory, it is believed that the T2 relaxation time is related to the mobility of each component, and that a shorter T2 relaxation time indicates a stronger interaction with matter. In one approach, the T2 relaxation time of the first component is shorter than that of the second component; for example, the T2 relaxation time of the first component is less than 0.6 ms, while that of the second component is greater than 1.2 ms. Based on the comparison of the T2 relaxation times of the first and second components, it is believed that the first component interacts with matter more strongly than the second component.

[0063] In one way, through 7 The chemical shift of the first component determined by Li NMR can be, for example, less than 0.6 ppm, further can be greater than -0.2 ppm and less than 0.55 ppm, and particularly can be greater than -0.15 ppm and less than 0.5 ppm. Additionally, by... 7 The chemical shift of the second component determined by Li NMR can, for example, be 0.6 ppm or more and 2.0 ppm or less, and more specifically, 0.7 ppm or more and 1.7 ppm or less. In one embodiment, 7 The reference substance for Li NMR determination is Li in a 1 mol / L LiCl aqueous solution.

[0064] In this invention, by means of 7 The chemical shift of the first component determined by Li NMR is expressed in 7 The chemical shift values ​​of the peaks belonging to the first component in the Li NMR spectrum. Similarly, through... 7 The chemical shift of the second component determined by Li NMR is expressed in 7 The chemical shift values ​​of the peaks attributed to the second component in the Li NMR spectrum. The chemical shift values ​​of the second component are greater than those obtained by passing through the Li NMR spectrum. 7 The chemical shift of the first component determined by Li NMR shows that the peak attributed to the second component is located relative to the peak attributed to the first component. 7 The low magnetic field side of the Li NMR spectrum. 7 In Li NMR, when peaks belonging to the first component overlap with peaks belonging to the second component, peak separation can be achieved using Lorentz curve regression.

[0065] The aforementioned Li atoms are representatively present on the aforementioned layer. That is, they can be in contact with the aforementioned layer, or they can exist on the aforementioned layer through other elements.

[0066] The content of Li atoms in the two-dimensional particles (e.g., the sum of the above-mentioned layers and the above-mentioned metal cations) may be, for example, 0.1% by mass or more and 20% by mass or less, further may be 0.1% by mass or more and 10% by mass or less, especially may be 0.2% by mass or more and 5% by mass or less, and particularly may be 0.2% by mass or more and 3% by mass or less.

[0067] The content of the aforementioned Li atoms can be determined, for example, by inductively coupled plasma atomic emission spectrometry (ICP-AES).

[0068] In one embodiment, the aforementioned two-dimensional particles contain phosphorus atoms. It is believed that by including phosphorus atoms, the Li atoms of the second component become readily present, thus readily exhibiting high electrical conductivity and high moisture resistance. The content of phosphorus atoms can, for example, be 0.1% by mass or more and 14% by mass or less, further 0.15% by mass or more and 5% by mass or less, and particularly 0.15% by mass or more and 1% by mass or less.

[0069] The aforementioned phosphorus atoms can exist, for example, in the form of anions containing phosphorus atoms, particularly in the form of PO4. 3- It exists in the form of phosphorus. Anions containing phosphorus atoms can bond with M in the above-mentioned layer. In addition, although not bound by a specific theory, it is considered that Li atoms loosely adsorbed on phosphorus-containing anions are equivalent to the second component mentioned above.

[0070] In one embodiment, the ratio of (average value of the major axis of the two-dimensional surface of the two-dimensional particle) to (average value of the thickness of the two-dimensional particle) is 1.2 or more, preferably 1.5 or more, and more preferably 2 or more. The average value of the major axis of the two-dimensional surface of the two-dimensional particle and the average value of the thickness of the two-dimensional particle can be obtained by the method described later.

[0071] (The average value of the major axis of the two-dimensional surface of a two-dimensional particle)

[0072] The average value of the major axis of the two-dimensional surface of the two-dimensional particle in this embodiment is 1 μm or more and 20 μm or less. Hereinafter, the average value of the major axis of the two-dimensional surface is sometimes referred to as the "average sheet size".

[0073] The larger the average flake size, the greater the conductivity of the conductive film. In this embodiment, the average flake size of the two-dimensional particles is as large as 1.0 μm or more; therefore, films formed using these two-dimensional particles, such as films obtained by stacking these two-dimensional particles, can achieve a conductivity of 2,000 S / cm or more. The average length of the two-dimensional surface is preferably 1.5 μm or more, more preferably 2.5 μm or more. When MXene is layered by ultrasonic treatment, most of the MXene is reduced to a length of approximately several hundred nm through ultrasonic treatment; therefore, it can be considered that the conductivity of the film formed from a single layer of MXene layered by ultrasonic treatment is relatively low.

[0074] From the viewpoint of dispersibility in the dispersion medium, the average value of the major axis of the two-dimensional surface is 20 μm or less, preferably 15 μm or less, and more preferably 10 μm or less.

[0075] As shown in the embodiments described later, the major axis of the two-dimensional surface refers to the major axis when each MXene particle is approximated as an ellipse in the electron microscope image, and the average value of the major axis of the two-dimensional surface refers to the average number of such major axes for 80 or more particles. Scanning electron microscopes (SEM) and transmission electron microscopes (TEM) images can be used as electron microscopes.

[0076] The average major and minor axes of the two-dimensional particles in this embodiment can be measured by dissolving the conductive film containing the two-dimensional particles in a solvent, thereby dispersing the two-dimensional particles in the solvent. Alternatively, it can be measured based on an SEM image of the conductive film.

[0077] (The average thickness of a two-dimensional particle)

[0078] The average thickness of the two-dimensional particles in this embodiment is preferably 1 nm or more and 15 nm or less. The aforementioned thickness is preferably 10 nm or less, more preferably 7 nm or less, and even more preferably 5 nm or less. On the other hand, considering the thickness of a single layer of MXene particles, the lower limit of the thickness of the two-dimensional particles can be 1 nm.

[0079] The average thickness of the two-dimensional particles was calculated as a number-average size (e.g., a digital average of at least 40) based on atomic force microscopy (AFM) or transmission electron microscopy (TEM) images.

[0080] (Implementation Method 2: Method for Manufacturing Two-Dimensional Particles)

[0081] The following describes in detail a method for manufacturing two-dimensional particles according to one embodiment of the present invention, but the present invention is not limited to this embodiment.

[0082] The method for manufacturing two-dimensional particles in this embodiment includes:

[0083] (a) Prepare the prescribed precursor.

[0084] (b) An etching process is performed, in which at least a portion of the A atoms are removed from the precursor using an etching solution.

[0085] (c) Performing a water rinsing process, which includes a step of rinsing the etched material obtained by the above-described etching process with water.

[0086] (d) Performing an intercalation process, which includes a step of mixing the water-washed product obtained by the above water washing with a metal-containing compound.

[0087] (e) A layering process is performed to obtain two-dimensional particles, wherein the layering process includes a step of stirring the intercalated material obtained by the above intercalation process.

[0088] The above etching solution contains phosphorus atoms.

[0089] The aforementioned metal-containing compounds contain at least Li atoms.

[0090] The following is a detailed description of each process.

[0091] Process (a)

[0092] First, the specified precursor is prepared. In this embodiment, the specified precursor that can be used is the MAX phase, which serves as a precursor to MXene.

[0093] From the following formula: M m AX n express,

[0094] (In the formula, M is at least one metal from Groups 3, 4, 5, 6, or 7.)

[0095] X is a carbon atom, a nitrogen atom, or a combination thereof.

[0096] A is at least one element from groups 12, 13, 14, 15, or 16.

[0097] n is 1 or more and 4 or less

[0098] (m is greater than n and less than 5).

[0099] M, X, n, and m are as described in the first embodiment. A is at least one element from Groups 12, 13, 14, 15, or 16, typically a Group A element, representative of Groups IIIA and IVA. More specifically, it may include at least one element selected from Al, Ga, In, Ti, Si, Ge, Sn, Pb, P, As, S, and Cd, preferably Al.

[0100] The MAX phase has a layer composed of A atoms located in M. m X n The crystal structure shown is between two layers (which can have X atoms located in an octahedral array of M atoms). The MAX phase is representative of layers with one layer of X atoms arranged between each of the layers with M atoms in the case of m = n+1 (these are also collectively referred to as "M"). m X n The repeating unit of a layer (“A-atom layer”) is configured as the next layer of the layer of M atoms, but is not limited to this.

[0101] The aforementioned MAX phase can be manufactured using known methods. For example, TiC powder, Ti powder, and Al powder are mixed using a ball mill, and the resulting mixed powder is sintered under an Ar atmosphere to obtain a sintered body (bulk MAX phase). Then, the sintered body is pulverized using an end mill to obtain a powdered MAX phase for the next process.

[0102] • Process (b)

[0103] In step (b), an etching solution is used to perform an etching process that removes at least a portion of the A atoms from the aforementioned precursor.

[0104] The aforementioned etching solution contains phosphorus atoms, and particularly phosphorus-containing anions. Therefore, phosphorus atoms, such as phosphorus atoms, and especially phosphorus-containing anions, can bond with M atoms. Furthermore, although not bound by a specific theory, it is believed that by including phosphorus atoms in the aforementioned etching solution, the Li atoms of the second component become more readily present. In addition, sufficient etching processing can be performed, making it easier to insert Li atoms in subsequent intercalation processes. The existence form of the aforementioned phosphorus-containing anions is not particularly limited; they can exist in ionic form or with H atoms. + It can exist as an acid by bonding, or as a salt by bonding with cations.

[0105] Examples of phosphorus-containing anions include PO42-. 3- .

[0106] The etching solution preferably contains H3PO4 and may further contain HF. A specific example of the etching solution is a mixture of an aqueous solution of HF and an aqueous solution of H3PO4. The etching solution may further contain HCl and LiF.

[0107] In the above etching solution, anions containing phosphorus atoms, especially PO4, are present. 3-The concentration can be, for example, above 2 mol / L and below 20 mol / L, further above 2.5 mol / L and below 18 mol / L, and especially above 3 mol / L and below 15 mol / L.

[0108] In the above etching solution, the concentration of HF can be, for example, above 2 mol / L and below 20 mol / L, more specifically above 2.5 mol / L and below 18 mol / L, and especially above 2.5 mol / L and below 15 mol / L.

[0109] Furthermore, in the aforementioned etching solution, the combined concentration of phosphorus-containing anions and HF can be, for example, 7 mol / L or more and 30 mol / L or less, more specifically 7.5 mol / L or more and 27 mol / L or less, and particularly 8 mol / L or more and 25 mol / L or less.

[0110] The etching operation and other conditions using the above-mentioned etching solution can be the same as those previously implemented.

[0111] Process (c)

[0112] The etched material obtained by the above etching process is rinsed with water. By rinsing with water, the acids and other substances used in the etching process can be thoroughly removed. There are no particular limitations on the amount of water mixed with the etched material or the rinsing method. Examples include adding water and stirring, centrifugation, etc. As stirring methods, examples include stirring with a hand crank, an automatic shaker, a shear mixer, a can mill, etc. The stirring speed, stirring time, etc., and the degree of stirring can be adjusted according to the amount or concentration of the acid being treated. The above water rinsing is performed once or more. It is preferable to perform water rinsing multiple times. For example, specifically, the following steps (i) to (iii) can be performed in the range of 2 or more, for example, 15 or less: (i) adding water and stirring (to the etched material or the remaining precipitate obtained in (iii) below), (ii) centrifuging the stirred material, and (iii) discarding the supernatant after centrifugation.

[0113] Process (d)

[0114] The intercalation process includes a step of mixing the water-washed material obtained by the above-mentioned water washing with a metal-containing compound containing metal ions. Thereby, metal ions are intercalated into the interlayer.

[0115] Examples of the aforementioned metal ions include monovalent metal ions, specifically alkali metal ions such as lithium ions, sodium ions, and potassium ions, copper ions, silver ions, and gold ions. Examples of metal-containing compounds containing the aforementioned metal ions include iodides, phosphates, sulfide salts containing sulfates, nitrates, acetates, and carboxylates of the aforementioned metal ions.

[0116] The aforementioned metal ions include at least lithium ions. Furthermore, as the metal-containing compound, a metal compound containing lithium ions is preferred, an ionic compound containing lithium ions is more preferred, and one or more of iodides, phosphates, and sulfide salts containing lithium ions are even more preferred, with phosphates containing lithium ions being particularly preferred. By using lithium ions as the metal ion, the resulting two-dimensional particles can become particles containing Li atoms.

[0117] In the intercalation treatment complex where the above-mentioned water-washed product is mixed with a metal-containing compound, the content of the metal-containing compound can be, for example, 0.001% by mass or more and 10% by mass or less, more preferably 0.01% by mass or more and 1% by mass or less, and especially preferably 0.1% by mass or more and 1% by mass or less. If the content of the metal-containing compound is within the above range, the dispersibility in the intercalation treatment complex is good.

[0118] The specific method for intercalation treatment is not particularly limited. For example, the water-washed material can be mixed with a metal-containing compound and stirred, or it can be left to stand. Stirring at room temperature is an example. The stirring methods mentioned above include, for example, using a stir bar, using a stirring blade, using a mixer, and using a centrifuge. The stirring time can be set according to the manufacturing scale of monolayer and few-layer MXene particles, for example, it can be set between 12 and 24 hours.

[0119] Process (e)

[0120] In step (e), a layering process is performed, which includes stirring the intercalated material obtained by the intercalation process. Through this layering process, monolayer or few-layer reduction of MXene particles can be achieved.

[0121] The conditions for stratification are not particularly limited and can be performed using known methods. For example, stirring methods include ultrasonic treatment, hand-shaking, and automatic shaking. The stirring speed, stirring time, and other degree of stirring can be adjusted according to the amount and concentration of the material to be treated. For example, after centrifuging the intercalated slurry and discarding the supernatant, pure water can be added to the remaining precipitate, and stratification can be performed by stirring, for example, by hand-shaking or using an automatic shaking device. The removal of unstripped material can be achieved by centrifuging, discarding the supernatant, and then washing the remaining precipitate with water. For example, (i) adding pure water to the remaining precipitate after discarding the supernatant and stirring, (ii) centrifuging, and (iii) recovering the supernatant can be achieved. By repeating the operations (i) to (ii) at least once, preferably at least twice and no more than ten times, a supernatant containing monolayer and few-layer MXene particles before acid treatment can be obtained as the stratified material. Alternatively, the supernatant can be centrifuged and discarded, and used as a stratified product to obtain clay containing monolayer and few-layer MXene particles before acid treatment.

[0122] In the manufacturing method of this embodiment, phosphorus atoms can coexist during layering. These phosphorus atoms can exist in the form of anions containing phosphorus atoms, or in the form of PO4. 3- It exists in the form of phosphoric acid. In this case, the pure water added to the precipitate can be a phosphoric acid aqueous solution. The pH of this phosphoric acid aqueous solution can be, for example, 2–5, or 2.5–4.5.

[0123] In one approach, phosphorus atoms can be coexisted only during layer separation and not during washing. For example, after centrifuging the intercalated slurry and discarding the supernatant, an aqueous phosphoric acid solution can be used instead of pure water added to the remaining precipitate, and pure water can be added in operation (i). Alternatively, in another approach, phosphorus atoms can be coexisted during both layer separation and washing. For example, after centrifuging the intercalated slurry and discarding the supernatant, an aqueous phosphoric acid solution can be used instead of pure water added to the remaining precipitate, and pure water can be added in operation (i).

[0124] In the manufacturing method of this embodiment, ultrasonic treatment is not required during the layering process. Without ultrasonic treatment, particle destruction is less likely to occur, and it is easier to obtain single-layer or few-layer MXene particles with a large two-dimensional plane parallel to the particle layer.

[0125] The layered material obtained by stirring can be used directly as two-dimensional particles containing monolayer and few-layer MXene particles, or it can be washed with water as needed.

[0126] (Implementation Method 3: Conductive Film)

[0127] As an example of the application of the two-dimensional particles in this embodiment, a conductive film containing two-dimensional particles can be cited. This conductive film exhibits high conductivity, high moisture resistance, and high smoothness. (See reference...) Figure 2 The conductive film of this embodiment will be described. Figure 2 The example shown illustrates a conductive film 30 obtained by simply stacking two-dimensional particles 10, but is not limited thereto. The conductive film may also include additives such as binders added during film formation, as needed. The proportion of the aforementioned additives in the conductive film (when dry) is preferably 30% by volume or less, more preferably 10% by volume or less, even more preferably 5% by volume or less, and most preferably 0% by volume.

[0128] As a method for producing a conductive film without using the aforementioned adhesives, a conductive film can be produced by filtering the supernatant containing two-dimensional particles obtained through the above-mentioned layering, or by spraying once or more a slurry of appropriate concentration containing two-dimensional particles mixed with a dispersion medium, followed by drying to remove the dispersion medium. The spraying method can be, for example, an airless spraying method or an air spraying method; specifically, methods using nozzles such as single-fluid nozzles, two-fluid nozzles, or spray guns can be used. Dispersion media that can be included in the slurry include water; organic media such as N-methylpyrrolidone, N-methylformamide, N,N-dimethylformamide, methanol, ethanol, dimethyl sulfoxide, ethylene glycol, and acetic acid.

[0129] Examples of such adhesives include acrylic resins, polyester resins, polyamide resins, polyolefin resins, polycarbonate resins, polyurethane resins, polystyrene resins, polyether resins, and polylactic acid.

[0130] The conductivity of the conductive film is preferably 2,000 S / cm or more, more preferably 5,000 S / m or more, even more preferably 10,000 S / cm or more, for example, it can be 100,000 S / cm or less, and even more preferably 50,000 S / cm or less.

[0131] The conductivity of the conductive film in this embodiment is obtained by substituting the thickness of the conductive film and the surface resistivity of the conductive film measured by the 4-probe method into the following formula.

[0132] Electrical conductivity [S / cm] = 1 / (thickness of conductive film [cm] × surface resistivity of conductive film [Ω / sq.])

[0133] (Implementation Method 4: Conductive Paste and Conductive Composite Material)

[0134] Other applications of the two-dimensional particles used in this embodiment include conductive pastes comprising the two-dimensional particles and, as needed, resins and additives (dispersion media, viscosity modifiers, etc.), and conductive composite materials comprising the two-dimensional particles and resins. These are also suitable for applications requiring high conductivity even under high humidity conditions.

[0135] Examples of resins that may be included in the aforementioned conductive pastes and conductive composite materials include resins that are the same as those that may be included in conductive films. Furthermore, examples of dispersion media that may be included in conductive pastes include water; organic media such as N-methylpyrrolidone, N-methylformamide, N,N-dimethylformamide, methanol, ethanol, dimethyl sulfoxide, ethylene glycol, and acetic acid.

[0136] (Implementation Method 5: Electrode)

[0137] The electrode in this embodiment includes the conductive film described above. The electrode may be formed solely of the conductive film, or it may include the conductive film and, for example, a substrate.

[0138] The electrode in this embodiment only needs to include the aforementioned conductive film, and its specific shape is not limited. Examples of electrodes range from solid electrodes to flexible, soft electrodes.

[0139] In the electrode of this embodiment, the conductive film can be exposed to the outside air in a manner that allows it to directly contact the object being measured, or it can be covered by a substrate or the like.

[0140] In this embodiment, when the electrode has a substrate, the conductive film can directly contact the substrate. The material of the substrate is not particularly limited; for example, it can be an inorganic material such as ceramic or glass, or an organic material. Examples of such organic materials include flexible organic materials, specifically thermoplastic polyurethane elastomer (TPU), PET film, and polyimide film. Alternatively, the substrate can be made of fibrous materials such as paper or cloth (e.g., sheet-like fibrous materials).

[0141] (Applications of electrodes)

[0142] The electrode of this embodiment can be used for any suitable application. Examples include counter electrodes for electrochemical measurements, reference electrodes, electrodes for electrochemical capacitors, electrodes for batteries, bioelectrodes, sensor electrodes, and antenna electrodes. It can also be used for applications requiring high conductivity (reducing initial conductivity loss and preventing oxidation), such as electromagnetic shielding (EMI shielding). Details of these applications will be provided below.

[0143] The electrodes are not particularly limited and can be, for example, electrodes for capacitors, electrodes for batteries, electrodes for biosignal sensing, electrodes for sensors, electrodes for antennas, etc. By using the above-mentioned conductive film, even with a smaller volume (device volume), it is possible to obtain large-capacity capacitors and batteries, low-impedance biosignal sensing electrodes, and high-sensitivity sensors and antennas.

[0144] Capacitors can be electrochemical capacitors. Electrochemical capacitors are capacitors that utilize the capacitance resulting from the physicochemical reaction between the electrodes (electrode active materials) and ions (electrolyte ions) in the electrolyte, and can be used as devices for storing electrical energy (energy storage devices). Batteries can be chemical batteries that can be repeatedly charged and discharged. Examples of batteries include lithium-ion batteries, magnesium-ion batteries, lithium-sulfur batteries, sodium-ion batteries, etc., but are not limited to these.

[0145] Biosignal sensing electrodes are electrodes used to acquire biological signals. Examples of biosignal sensing electrodes include, but are not limited to, electrodes used to measure EEG (electroencephalography), ECG (electrocardiography), EMG (electromyography), and EIT (electrophysiological testing).

[0146] Sensor electrodes are used to inspect target substances, states, anomalies, etc. Sensors can be, for example, gas sensors, biosensors (chemical sensors that utilize biologically derived molecular recognition mechanisms), etc., but are not limited to these.

[0147] Antenna electrodes are used to radiate electromagnetic waves into space and / or receive electromagnetic waves in space. Antennas constructed from antenna electrodes include mobile communication antennas (such as those used in mobile phones, i.e., 3G, 4G, and 5G), RFID antennas, or NFC (Near Field Communication) antennas, etc., without any particular limitation.

[0148] The electrode in this embodiment is preferably used as an antenna electrode. The electrode comprising the aforementioned conductive film has high conductivity and high moisture resistance, and as a conductive film, it also exhibits high smoothness. Electrodes with these characteristics can be advantageously used to extend communication distances.

[0149] The two-dimensional particles of one embodiment of the present invention have been described in detail above, but various modifications can be made. It should be noted that the two-dimensional particles of the present invention can also be manufactured by methods different from those described in the above embodiments. Furthermore, it should be observed that the manufacturing method of the two-dimensional particles of the present invention is not limited to providing the two-dimensional particles of the above embodiments.

[0150]

Example

[0151] The invention is illustrated in more detail by way of the following embodiments, but the invention is not limited to these embodiments.

[0152] [Examples 1-8, Comparative Examples 1-2]

[0153] [The creation of two-dimensional particles]

[0154] In Examples 1-8 and Comparative Examples 1-2, the following detailed steps were performed sequentially: (1) preparation of the precursor (MAX), (2) etching of the precursor, (3) cleaning, (4) intercalation, (5) layering, and (6) water cleaning to create two-dimensional particles.

[0155] (1) Preparation of precursor (MAX)

[0156] TiC powder, Ti powder, and Al powder (all manufactured by High Purity Chemical Research Institute, Ltd.) were added to a ball mill containing zirconia balls in a molar ratio of 2:1:1 and mixed for 24 hours. The resulting mixed powder was calcined at 1,350°C for 2 hours under an Ar atmosphere. The resulting calcined body (block) was then pulverized with an end mill to a maximum size of less than 40 μm. Thus, Ti3AlC2 particles were obtained as a precursor (MAX).

[0157] (2) Etching of the precursor

[0158] Using Ti3AlC2 particles (powder) prepared by the above method, etching was performed under the following etching conditions to obtain a solid-liquid mixture (slurry) containing solid components from Ti3AlC2 powder.

[0159] (Etching conditions)

[0160] • Precursor: Ti3AlC2 (passed through a sieve with a mesh size of 45μm)

[0161] • The composition of the etching solution is shown in Table 1.

[0162] • Precursor dosage: 3.0g

[0163] • Etched container: 100mL bottle (Aiboy)

[0164] • Etching temperature: 35℃

[0165] • Etching time: 24 hours

[0166] • Mixer speed: 400 rpm

[0167] (3) Cleaning

[0168] The above slurry was divided into two portions and inserted into two 50 mL centrifuge tubes respectively. After centrifugation at 3500 G for 5 minutes, the supernatant was discarded. 35 mL of pure water was added to each centrifuge tube, and the mixture was centrifuged again at 3500 G for 5 minutes to remove the supernatant. This operation was repeated 11 times. Finally, after centrifugation, the supernatant was discarded, yielding Ti3C2T. s - Moisture-rich clay medium.

[0169] (4) Intercalation

[0170] For Ti3C2T prepared by the above method s A water-based clay medium was prepared by adding 5.3 g of 85% (w / w) phosphoric acid aqueous solution, 0.68 g of Li3PO4, and 31.9 g of pure water. The mixture was stirred at a temperature above 20°C and below 25°C for 24 hours to perform intercalation using lithium ions as the intercalating agent. The detailed intercalation conditions are as follows.

[0171] (Conditions for intercalation)

[0172] ·Ti3C2T s - Moisture-modified clay (after washing MXene): Solid content 0.5g

[0173] • Metal-containing compounds: 0.68g of Li3PO4

[0174] • Intercalation container: 100mL bottle

[0175] Temperature: Above 20℃ and below 25℃ (room temperature)

[0176] • Time: 24 hours

[0177] • Mixer speed: 700 rpm

[0178] (5) Layering

[0179] The slurry obtained from intercalation was placed in a 50 mL centrifuge tube and centrifuged at 3,500 G for 5 minutes. The supernatant was then collected. Next, 35 mL of a phosphoric acid aqueous solution adjusted to pH 3.5 was added, and the mixture was stirred for 15 minutes. After centrifugation at 3,500 G for 5 minutes, the supernatant was collected as the liquid containing monolayer MXene particles. This operation was repeated four times to obtain a supernatant containing monolayer MXene particles. Finally, this supernatant was centrifuged at 4,300 G for 2 hours. The supernatant was discarded, yielding clay containing two-dimensional particles (monolayer MXene particles).

[0180] [Example 9]

[0181] After performing the preparation, etching, cleaning and layering processes of the precursor (MAX) in the same manner as in Example 1, the following process (5) is performed to produce clay containing two-dimensional particles (single-layer MXene particles).

[0182] (1) Preparation of precursor (MAX): Same as in Examples 1-8

[0183] (2) Etching of the precursor: Same as in Examples 1-8

[0184] (3) Cleaning: Same as in Example 1

[0185] (4) Intercalation: Same as in Examples 1-8

[0186] (5) Layering

[0187] The slurry obtained by intercalation was placed in a 50 mL centrifuge tube and centrifuged at 3500 G for 5 minutes to obtain a supernatant. This supernatant was then centrifuged at 4,300 G for 2 hours, and the supernatant was discarded to obtain clay containing two-dimensional particles (monolayer MXene particles).

[0188] [Example 10]

[0189] After performing the same preparation, etching, cleaning and layering processes as in Example 1, the following process (5) was performed to produce clay containing two-dimensional particles (single-layer MXene particles).

[0190] (1) Preparation of precursor (MAX): Same as in Examples 1-8

[0191] (2) Etching of the precursor: Same as in Examples 1-8

[0192] (3) Cleaning: Same as in Example 1

[0193] (4) Intercalation: Same as in Examples 1-8

[0194] (5) Layering

[0195] The slurry obtained from intercalation was placed in a 50 mL centrifuge tube and centrifuged at 3,500 G for 5 minutes. The supernatant was then recovered, yielding clay containing two-dimensional particles (monolayer MXene particles). Additionally, 35 mL of pure water was added, and the mixture was stirred for 15 minutes. It was then centrifuged at 3,500 G for 5 minutes, and the supernatant was recovered as a liquid containing monolayer MXene particles. This supernatant was then centrifuged at 4,300 G for 2 hours, and the supernatant was discarded, yielding clay containing two-dimensional particles (monolayer MXene particles).

[0196] [Example 11]

[0197] After performing the same preparation, etching, cleaning and layering processes as in Example 1, the following process (5) was performed to produce clay containing two-dimensional particles (single-layer MXene particles).

[0198] (1) Preparation of precursor (MAX): Same as in Examples 1-8

[0199] (2) Etching of the precursor: Same as in Examples 1-8

[0200] (3) Cleaning: Same as in Example 1

[0201] (4) Intercalation: Same as in Examples 1-8

[0202] (5) Layering

[0203] The slurry obtained from intercalation was placed in a 50 mL centrifuge tube and centrifuged at 3,500 G for 5 minutes. The supernatant was collected to obtain clay containing two-dimensional particles (monolayer MXene particles). Then, 35 mL of pure water was added, and the mixture was stirred for 15 minutes. After centrifugation at 3,500 G for 5 minutes, the supernatant was collected as the liquid containing monolayer MXene particles. This operation was repeated twice to obtain a supernatant containing monolayer MXene particles. Finally, this supernatant was centrifuged at 4,300 G for 2 hours. The supernatant was discarded, yielding clay containing two-dimensional particles (monolayer MXene particles).

[0204] [Example 1 2]

[0205] After performing the same preparation, etching, cleaning and layering processes as in Example 1, the following process (5) was performed to produce clay containing two-dimensional particles (single-layer MXene particles).

[0206] (1) Preparation of precursor (MAX): Same as in Examples 1-8

[0207] (2) Etching of the precursor: Same as in Examples 1-8

[0208] (3) Cleaning: Same as in Example 1

[0209] (4) Intercalation: Same as in Examples 1-8

[0210] (5) Layering

[0211] The slurry obtained from intercalation was placed in a 50 mL centrifuge tube and centrifuged at 3,500 G for 5 minutes. The supernatant was collected to obtain clay containing two-dimensional particles (monolayer MXene particles). Then, 35 mL of pure water was added, and the mixture was stirred for 15 minutes. After centrifugation at 3,500 G for 5 minutes, the supernatant was collected as the liquid containing monolayer MXene particles. This operation was repeated three times to obtain a supernatant containing monolayer MXene particles. Finally, this supernatant was centrifuged at 4,300 G for 2 hours. The supernatant was discarded, yielding clay containing two-dimensional particles (monolayer MXene particles).

[0212] [Example 13]

[0213] After performing the same preparation, etching, cleaning and layering processes as in Example 1, the following process (5) was performed to produce clay containing two-dimensional particles (single-layer MXene particles).

[0214] (1) Preparation of precursor (MAX): Same as in Examples 1-8

[0215] (2) Etching of the precursor: Same as in Examples 1-8

[0216] (3) Cleaning: Same as in Example 1

[0217] (4) Intercalation: Same as in Examples 1-8

[0218] (5) Layering

[0219] The slurry obtained from intercalation was placed in a 50 mL centrifuge tube and centrifuged at 3,500 G for 5 minutes. The supernatant was collected to obtain clay containing two-dimensional particles (monolayer MXene particles). Then, 35 mL of pure water was added, and the mixture was stirred for 15 minutes. After centrifugation at 3,500 G for 5 minutes, the supernatant was collected as the liquid containing monolayer MXene particles. This operation was repeated four times to obtain a supernatant containing monolayer MXene particles. Finally, this supernatant was centrifuged at 4,300 G for 2 hours. The supernatant was discarded, yielding clay containing two-dimensional particles (monolayer MXene particles).

[0220] [Comparative Example 3]

[0221] After preparing the precursor (MAX) in the same manner as in Example 1, the following (2) process was performed. The cleaning process was performed in the same manner as in Example 1. The following (4) and (5) processes were further performed to produce clay containing two-dimensional particles (single-layer MXene particles).

[0222] (1) Preparation of precursor (MAX): Same as in Example 1

[0223] (2) Etching of the precursor

[0224] Using the Ti3AlC2 particles (powder) prepared in the above (1) process, etching was performed under the following etching conditions to obtain a solid-liquid mixture (slurry) containing solid components from the Ti3AlC2 powder.

[0225] (Etching conditions)

[0226] • Precursor: Ti3AlC2 (passed through a sieve with a mesh size of 45μm)

[0227] • Etching solution composition: 49% HF 6mL

[0228] 18mL H2O

[0229] HCl (12M) 36mL

[0230] • Precursor dosage: 3.0g

[0231] • Etched container: 100mL bottle

[0232] • Etching temperature: 35℃

[0233] Etching time: 24 hours

[0234] • Mixer speed: 400 rpm

[0235] (3) Cleaning: Same as in Example 1

[0236] (4) Intercalation

[0237] For Ti3C2T prepared by the above method s - A water-based clay medium was prepared by adding 0.75g of LiCl and 37.2g of pure water, and stirring at a temperature above 20°C and below 25°C for 24 hours to perform intercalation using lithium ions as the intercalating agent. Detailed intercalation conditions are described below.

[0238] (Conditions for intercalation)

[0239] ·Ti3C2T s - Moisture-modified clay (after washing MXene): Solid content 0.5g

[0240] • Metal-containing compounds: 0.75g of LiCl

[0241] • Intercalation container: 100mL bottle

[0242] Temperature: Above 20℃ and below 25℃ (room temperature)

[0243] • Time: 24 hours

[0244] • Mixer speed: 700 rpm

[0245] (5) Layering

[0246] The slurry obtained from intercalation was placed in a 50 mL centrifuge tube and centrifuged at 3,500 G for 5 minutes. The supernatant was collected to obtain clay containing two-dimensional particles (monolayer MXene particles). Then, 35 mL of pure water was added, and the mixture was stirred for 15 minutes. After centrifugation at 3,500 G for 5 minutes, the supernatant was collected as the liquid containing monolayer MXene particles. This operation was repeated four times to obtain a supernatant containing monolayer MXene particles. Finally, this supernatant was centrifuged at 4,300 G for 2 hours. The supernatant was discarded, yielding clay containing two-dimensional particles (monolayer MXene particles).

[0247] [Comparative Example 4]

[0248] After preparing the precursor (MAX) in the same manner as in Example 1, the following steps (2) are performed, followed by a cleaning process, and then the following steps (5) are performed to produce clay containing two-dimensional particles (single-layer MXene particles).

[0249] (1) Preparation of precursor (MAX): Same as in Example 1

[0250] (2) Etching and intercalation of the precursor

[0251] Using the Ti3AlC2 particles (powder) prepared in the above (1) process, etching was performed under the following etching conditions to obtain a solid-liquid mixture (slurry) containing solid components from the Ti3AlC2 powder.

[0252] (Etching and intercalation conditions)

[0253] • Precursor: Ti3AlC2 (passed through a sieve with a mesh size of 45μm)

[0254] • Etching solution composition: LiF 3g

[0255] HCl (9M) 30mL

[0256] • Precursor dosage: 3.0g

[0257] • Etched container: 100mL bottle

[0258] • Etching temperature: 35℃

[0259] Etching time: 24 hours

[0260] • Mixer speed: 400 rpm

[0261] (3) Cleaning: Same as in Example 1

[0262] (5) Layering

[0263] The slurry obtained from intercalation was placed in a 50 mL centrifuge tube and centrifuged at 3,500 G for 5 minutes. The supernatant was collected to obtain clay containing two-dimensional particles (monolayer MXene particles). Then, 35 mL of pure water was added, and the mixture was stirred for 15 minutes. After centrifugation at 3,500 G for 5 minutes, the supernatant was collected as the liquid containing monolayer MXene particles. This operation was repeated four times to obtain a supernatant containing monolayer MXene particles. Finally, this supernatant was centrifuged at 4,300 G for 2 hours. The supernatant was discarded, yielding clay containing two-dimensional particles (monolayer MXene particles).

[0264] [Compare Examples 5 and 6]

[0265] After performing the same preparation, etching, cleaning and layering processes as in Example 1, the following process (5) was performed to produce clay containing two-dimensional particles (single-layer MXene particles).

[0266] (1) Preparation of precursor (MAX): Same as in Examples 1-8

[0267] (2) Etching of the precursor: Same as in Examples 1-8

[0268] (3) Cleaning: Same as in Example 1

[0269] (4) Intercalation: Same as in Examples 1-8

[0270] (5) Layering

[0271] The slurry obtained from intercalation was placed in a 50 mL centrifuge tube and centrifuged at 3,500 G for 5 minutes. The supernatant was collected to obtain clay containing two-dimensional particles (monolayer MXene particles). Then, 35 mL of pure water was added, and the mixture was stirred for 15 minutes. After centrifugation at 3,500 G for 5 minutes, the supernatant was collected as the liquid containing monolayer MXene particles. This operation was repeated four times to obtain a supernatant containing monolayer MXene particles. Finally, this supernatant was centrifuged at 4,300 G for 2 hours. The supernatant was discarded, yielding clay containing two-dimensional particles (monolayer MXene particles).

[0272] (Method for determining phosphorus atom content)

[0273] The clays containing two-dimensional particles (monolayer MXene particles) obtained in Examples 1-13 and Comparative Examples 1-6 were subjected to vacuum filtration. After filtration, the clays were vacuum dried at 80°C for 24 hours to prepare a conductive membrane containing two-dimensional particles. A membrane filter (Merck, Durapore, 0.45 μm pore size) was used for vacuum filtration. The supernatant contained 0.05 g of solids (two-dimensional particles) and 40 mL of pure water.

[0274] The obtained conductive film containing two-dimensional particles was analyzed using X-ray photoelectron spectroscopy (XPS) to determine the phosphorus atom content in the two-dimensional particles. The XPS measurements were performed using a Quantum 2000 instrument manufactured by ULVAC-PHI.

[0275] The phosphorus atom content in the two-dimensional particles was 0.20% by mass in Example 1, 0.25% by mass in Example 2, 0.32% by mass in Example 3, 0.34% by mass in Example 4, 0.14% by mass in Comparative Example 1, 0.18% by mass in Comparative Example 2, 0.20% by mass in Comparative Example 5, and 0.34% by mass in Comparative Example 6.

[0276] (Method for determining the Li atom content)

[0277] The metal cations contained in the two-dimensional particles (monolayer MXene particles) obtained in Examples 1-13 and Comparative Examples 1-6 were determined by inductively coupled plasma atomic emission spectrometry (ICP-AES) using a Thermo Fisher Scientific iCAP7400.

[0278] The content of Li atoms in the two-dimensional particles was 0.30% by mass in Example 1.

[0279] [Table 1]

[0280]

[0281] ( 7 Li NMR determination method: quantification of component 1 and component 2)

[0282] In an Ar atmosphere (dew point less than -60°C) glove box, two-dimensional particles (monolayer MXene particles) and dried Al2O3 powder were mixed at a mass ratio of 1:9 and pulverized using an agate mortar to obtain a mixed powder. Inside the glove box, the mixed powder was filled into a 4 mm outer diameter solid NMR zirconia sample tube and capped with a Kel-F cap, serving as the NMR sample. The total sample volume of the two-dimensional particles (monolayer MXene particles) and Al2O3 powder was 200 mg.

[0283] As 7 The Li NMR apparatus (spectrometer) used was an AVANCE III 400 manufactured by Bruker (magnetic field strength 9.4T). 7 The Li nucleus resonant frequency is 155.455 MHz. A Bruker PH MAS 400S1 BL4N-P / H VTN detector was used as the detector.

[0284] Implemented under the following conditions 7 Li NMR measurements yielded a one-dimensional [structure / data]. 7 Li NMR spectrum.

[0285] Measurement method: Magic angle rotation + single pulse method

[0286] Magic horn rotation speed: 15kHz

[0287] Pulse intensity: 28–56 kHz (output power fixed at 100 W)

[0288] Pulse flip angle: 90°

[0289] Total delay time: 4 seconds

[0290] Total number of times: 1,024

[0291] For what was obtained 7 The Li NMR spectrum was regressed using Lorentz curves for two components to determine the chemical shifts and relative areas of each peak. The reference substance was Li in a 1 mol / L LiCl aqueous solution. The regression calculations, chemical shift values, and relative areas of Li were performed using the spectral fitting function included in Bruker's NMR console software. Peaks belonging to components 1 and 2 were determined based on their chemical shift values. The proportion of component 1 (atomic reference) was calculated as S1 / (S1+S2) based on the relative areas S1 and S2 of the peaks belonging to component 1. The results are shown in Table 2.

[0292] [Table 2]

[0293]

[0294] In the two-dimensional particles of the examples, the proportion of the first component in the total of the first and second components is in the range of 17 atomic% or more and 70 atomic% or less. Specifically, in Examples 4 and 5, an aqueous phosphoric acid solution was used during layering; however, in Examples 9-13, an aqueous phosphoric acid solution was not used during layering, and only pure water was used. In Examples 4 and 5 and Examples 9-13, the etching conditions were different, therefore the surface state of the MXene layer was different. It is believed that in Examples 9-13, by layering with only pure water, two-dimensional particles in which the proportion of the first component in the total of the first and second components is 17 atomic% or more and 70 atomic% or less were obtained. On the other hand, in the two-dimensional particles of Comparative Examples 3 and 4, the proportion of the first component in the total of the first and second components exceeds 70 atomic%, while in the two-dimensional particles of Comparative Examples 5 and 6, the first component was not detected.

[0295] ( 7 Li NMR determination method: Determination of T2 relaxation time)

[0296] For the two-dimensional particles of Examples 5 and Comparative Examples 2-4, NMR samples were prepared in the same manner as for the quantification of the first and second components, using the same methods as for the quantification of the first and second components. 7 Li NMR apparatus.

[0297] Implemented under the following conditions 7 Li NMR measurements yielded a one-dimensional [structure / data]. 7 Li NMR spectrum.

[0298] Measurement method: Magic angle rotation + CPMG method

[0299] Magic angle spinning speed: 12.5kHz

[0300] Pulse intensity: 28 to 56kHz (output power is fixed at 100W)

[0301] Echo time: 160μs

[0302] Number of echoes: 48

[0303] Accumulation delay time: 4 seconds

[0304] Number of accumulations: 1,024

[0305] For the real component obtained by performing phase correction on the acquired time-domain data, the relative area of each echo is plotted against the refocusing time. The echo decay curve is regressed using the sum of exponential functions fixed with the relative areas of the first component and the second component obtained in the above quantitative measurement as the coefficient ratio, to obtain each time constant (T2 relaxation time).

[0306] In the two-dimensional particles of Example 5, the T2 relaxation time of the first component is 0.47ms, and the T2 relaxation time of the second component is 1.7ms. In the two-dimensional particles of Comparative Example 2, the T2 relaxation time of the first component is 0.36ms, and the T2 relaxation time of the second component is 2ms. In the two-dimensional particles of Comparative Example 3, the T2 relaxation time of the first component is 0.56ms, and the T2 relaxation time of the second component is 1.5ms. In the two-dimensional particles of Comparative Example 4, the T2 relaxation time of the first component is 0.44ms, and the T2 relaxation time of the second component is 1.2ms. Among these two-dimensional particles, the T2 relaxation time of the first component is shorter than the T2 relaxation time of the second component, and it is considered that the first component strongly interacts with the substance.

[0307] (Method 1 for producing conductive composite film)

[0308] To 50g of the dispersion of the two-dimensional particles of Example 5 (concentration of two-dimensional particles (MXene solid content): 6.4 mass%), 52.750g of a solution prepared by diluting a polyurethane solution (manufactured by Dainichiseika Color & Chemicals Mfg. Co., Ltd., non-volatile content concentration 35 mass%) 100 times with pure water was added to prepare a composite. Then, the composite was stirred for 15 minutes using an automatic shaker (SK550 manufactured by F&FM Co.). A polyimide film (Kapton film manufactured by DU PONT-TORAY Co., Ltd.) was prepared, the surface of the polyimide film was hydrophilized by oxygen plasma treatment (PC-1000 manufactured by Samco Inc.), and then the above composite was sprayed onto the film 30 times. It should be noted that each spray coating was dried for 2 minutes using a dryer. A nozzle manufactured by ATOMAX Co. was used as the spray nozzle.

[0309] After coating, the film was dried in an oven at 80°C under normal pressure for 2 hours, and then dried overnight in a vacuum oven at 150°C to obtain the sprayed film. The resulting composite sprayed film had a thickness of 4.4 μm, and its initial conductivity, measured by the conductivity measurement method described later, was 17,668 S / cm. Furthermore, after a 14-day moisture resistance test at room temperature and 99% humidity, the conductivity was similarly measured to be 8,127 S / cm, representing a change of 46% relative to the initial conductivity.

[0310] To 25.221 g of the two-dimensional particle dispersion of Comparative Example 3 (two-dimensional particle (MXene solid component) concentration: 3.25 wt%), 14.779 g of a solution prepared by diluting a polyurethane solution (manufactured by Daihatsu Seika Co., Ltd., non-volatile component concentration 35 wt%) 100 times with pure water was added to form a composite. The composite was then stirred for 15 minutes using an automatic shaker (F&FM SK550). A polyimide film (DU PONT-TORAY Kapton film) was prepared, and its surface was hydrophilized by oxygen plasma treatment (Samco PC-1000). The composite was then sprayed onto the film 30 times. It should be noted that each coating was dried in a dryer for 2 minutes. An ATOMAX nozzle was used for spraying.

[0311] After coating, the film was dried in an oven at 80°C under normal pressure for 2 hours, and then dried overnight in a vacuum oven at 150°C to obtain the sprayed film. The resulting composite sprayed film had a thickness of 3.2 μm, and its initial conductivity, measured by the conductivity measurement method described later, was 10,269 S / cm, which is lower than that obtained using the two-dimensional particles in Example 5. Furthermore, after a 14-day moisture resistance test at room temperature and 99% humidity, the conductivity was similarly measured to be 3,081 S / cm, representing a change of 30% relative to the initial conductivity.

[0312] As confirmed above, the conductive composite film containing two-dimensional particles in Example 5 exhibits high initial conductivity and good moisture resistance. On the other hand, in the two-dimensional particles of Comparative Example 3, the proportion of the first component in the total of the first and second components exceeds 70 atomic percent, which is insufficient to adequately satisfy the requirements for initial conductivity and moisture resistance.

[0313] (Method 1 for manufacturing conductive films)

[0314] 0.5 g of clay containing two-dimensional particles (monolayer MXene particles) obtained in Examples 4, 6, 7, and Comparative Examples 3 and 4 was mixed with 15 mL of pure water and then filtered using a Buchner funnel. After filtration, the mixture was vacuum dried at 80°C for 24 hours to prepare a conductive membrane containing two-dimensional particles. A membrane filter (0.22 μm pore size) was used for the vacuum filtration.

[0315] The conductive film containing the two-dimensional particles obtained in Example 4 has a film density of 3.6 g / cm³. 3 The conductivity is 14,000 S / cm. The film density of the conductive film containing the two-dimensional particles obtained in Example 6 is 3.7 g / cm³. 3 The conductivity is 15,700 S / cm, and the conductivity change rate is 95%. The film density of the conductive film containing the two-dimensional particles obtained in Example 7 is 3.2 g / cm³. 3 The conductivity was 13,600 S / cm, and the rate of change of conductivity was 94%. The film density of the conductive film containing the two-dimensional particles obtained in Comparative Example 3 was 2 g / cm³. 3 The conductivity is 9,000 S / cm, and the conductivity change rate is 78%. The film density of the conductive film containing the two-dimensional particles obtained in Comparative Example 4 is 2 g / cm³. 3 The conductivity is 6,000 S / cm, and the conductivity change rate is 23.

[0316] As confirmed above, the conductive film containing the two-dimensional particles obtained in the examples has high conductivity and good moisture resistance. On the other hand, in Comparative Examples 3 and 4, the proportion of the first component in the total of the first and second components exceeds 70 atomic percent, and the conductivity and conductivity change rate of the resulting conductive film cannot be sufficiently satisfied.

[0317] (Method 2 for manufacturing conductive films)

[0318] Clay containing the two-dimensional particles (monolayer MXene particles) obtained in Examples 1-13 was coated onto a polyethylene terephthalate film (manufactured by TORAY, Lumirror) to a thickness of 120 μm or less. Then, it was air-dried to obtain a conductive film formed by coating. The thickness of the obtained conductive film was 1 μm.

[0319] (Method 3 for manufacturing conductive films)

[0320] 0.5 g of clay containing two-dimensional particles (monolayer MXene particles) obtained in Examples 1-13 was mixed with 4 mL of pure water. Then, the mixture was sprayed onto a polyethylene terephthalate film (TORAY, Lumirror) 1-30 times using a spray gun (Tamiya air brush). Each spray coating was dried in a dryer for 2 minutes. After coating, the film was dried in an oven at 80°C for 2 hours, and then dried overnight in a vacuum oven at 150°C to obtain the sprayed film.

[0321] The film density, conductivity, and rate of change of conductivity of the conductive film were determined by the following methods.

[0322] (Method for measuring thin film density)

[0323] The film is punched into pieces with a diameter of 12 mmφ, its weight is measured using an electronic balance, and its thickness is measured using an altimeter. The film density is calculated based on the obtained values.

[0324] (Methods for measuring the conductivity of conductive films)

[0325] The conductivity of the obtained conductive film containing two-dimensional particles was determined. Regarding conductivity, resistivity (Ω) and thickness (μm) were measured at three locations on a single sample. The conductivity (S / cm) was calculated from these measurements, and the average of the three conductivity values ​​was used. For resistivity measurement, a simple low resistivity meter (Loresta AX MCP-T370, Mitsubishi Chemical Analytech, Ltd.) was used to measure the surface resistance of the conductive film using the four-terminal method. Thickness measurement was performed using a micrometer (MDH-25MB, Mitutoyo, Ltd.). Then, the volume resistivity was calculated based on the obtained surface resistance and conductive film thickness. The reciprocal of this value was taken to determine the conductivity, which was denoted as E0.

[0326] (Method for measuring the rate of change of electrical conductivity)

[0327] A conductive film was placed in a constant temperature and humidity bath at 99% relative humidity and 25℃. After standing for 7 days, the conductivity was measured and denoted as E. E divided by E0 was taken as the rate of change of conductivity.

[0328] Explanation of reference numerals in the attached figures

[0329] 1a and 1b main body (M) m X n layer)

[0330] 3a, 5a, 3b, 5b Modifications or terminal T

[0331] 7a, 7b MXene layers

[0332] 10, 10a, 10b MXene particles (two-dimensional particles of layered materials)

Claims

1. A two-dimensional particle, which is a two-dimensional particle having one or more layers, The two-dimensional particle contains Li atoms. The layer comprises the following formula: M m X n The layer body shown and the decoration or end T present on the surface of the layer body, wherein, T is selected from at least one of the following: hydroxyl, fluorine, chlorine, oxygen, and hydrogen. Formula M m X n In this context, M is at least one metal from Groups 3, 4, 5, 6, or 7. X is a carbon atom, a nitrogen atom, or a combination thereof. n is 1 or more and 4 or less m is greater than n and less than 5 Li atoms contain the first component and through 7 The second component, whose chemical shift is greater than that of the first component as determined by Li NMR, The proportion of the first component in the total of the first component and the second component is 17 atomic% or more and 70 atomic% or less.

2. The two-dimensional particle according to claim 1, wherein, Through the above 7 The chemical shift of the first component, as determined by Li NMR, is less than 0.6 ppm. 7 The chemical shift of the second component, as determined by Li NMR, is greater than 0.6 ppm and less than 2.0 ppm.

3. The two-dimensional particle according to claim 1 or 2, comprising phosphorus atoms.

4. The two-dimensional particle according to claim 3, wherein, The phosphorus atoms are present in a concentration of 0.1% by mass or more and 14% by mass or less.

5. The two-dimensional particle according to claim 3, wherein, The phosphorus atom is PO4. 3- Its form.

6. The two-dimensional particle according to claim 1 or 2, wherein the average thickness is more than 1 nm and less than 10 nm.

7. A conductive film comprising two-dimensional particles according to any one of claims 1 to 6.

8. A conductive paste comprising the two-dimensional particles according to any one of claims 1 to 6.

9. A conductive composite material comprising two-dimensional particles and resin as described in any one of claims 1 to 6.

10. The method for manufacturing two-dimensional particles according to claim 1, comprising: (a) Preparation of a precursor, wherein the precursor is M m AX n express, In the formula, M is at least one metal from Groups 3, 4, 5, 6, or 7, and contains at least Ti. X is a carbon atom, a nitrogen atom, or a combination thereof. A is at least one element from groups 12, 13, 14, 15, or 16. n is 1 or more and 4 or less m is greater than n and less than 5 (b) An etching process is performed, in which at least a portion of the A atoms are removed from the precursor using an etching solution. (c) Performing a water rinsing process, which includes a step of rinsing the etched material obtained by the etching process with water. (d) Performing an intercalation process, which includes a step of mixing the water-washed material obtained by the water washing with a metal-containing compound. (e) Obtaining two-dimensional particles by performing a layering process, which includes a step of stirring the intercalated material obtained by the intercalation process. The etching solution contains phosphorus atoms. The metal-containing compound contains at least Li atoms.

Citation Information

Patent Citations

  • Virus-inactivating liquid agent and virus-inactivating article

    WO2022138456A1

  • Two-dimensional particle, method for producing two-dimensional particle, and material

    WO2023162423A1